1998
DOI: 10.1021/ac980690d
|View full text |Cite
|
Sign up to set email alerts
|

Routine Part-per-Million Mass Accuracy for High- Mass Ions:  Space-Charge Effects in MALDI FT-ICR

Abstract: The effect of ion space-charge on mass accuracy in Fourier transform ion cyclotron resonance mass spectrometry is examined. Matrix-assisted laser desorption/ionization is used to form a population of high-molecular-weight polymer ions with a wide mass distribution. The density of the ions in the analyzer cell is varied using ion remeasurement and suspended trapping techniques to allow the effect of ion space charge to be examined independently of other experimental influences. Observed cyclotron frequency exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
185
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(191 citation statements)
references
References 42 publications
6
185
0
Order By: Relevance
“…The role of the ion space charge becomes increasingly important for LC-FTICR studies because both the total ion population and specific ion abundances may vary in a wide range. A systematic study of the mass accuracy under such conditions [9] has demonstrated that the frequency correction based on the overall intensity can improve the FTICR mass measurement accuracy over a wide mass range for externally calibrated spectra.…”
Section: Correction For the Frequency Shiftsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the ion space charge becomes increasingly important for LC-FTICR studies because both the total ion population and specific ion abundances may vary in a wide range. A systematic study of the mass accuracy under such conditions [9] has demonstrated that the frequency correction based on the overall intensity can improve the FTICR mass measurement accuracy over a wide mass range for externally calibrated spectra.…”
Section: Correction For the Frequency Shiftsmentioning
confidence: 99%
“…However, the mass accuracy in an FTICR experiment depends crucially on the number of ions used for the measurement [9,[11][12][13][14][15][16][17][18]. When online separations are used, the analyte ion production rates vary widely, and the ion population in the trap cannot be easily or precisely controlled.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 For example, Amster and co-workers developed a calibration curve to account for the difference between ion populations of the calibration spectrum and subsequent spectra resulting in <10 parts-per-million MMA. 23 calibration law which afforded <5 ppm MMA. 26 Amster and co-workers recently developed stepwise-external calibration, in which calibration spectra are acquired at low trapping voltages, and experimental spectra are acquired at more routine trapping voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) [15][16][17][18][19][20] is known for its unparalleled mass accuracy and mass resolution and has become an important tool in many areas of analytical life sciences [21,22]. For this reason, the FT-ICR MS technique has been combined with the soft ionization technique MALDI using internal [23][24][25][26][27][28] as well as external [29 -37] ion sources. One of the striking advantages of the MALDI FT-ICR technique is high sensitivity as well as high throughput capability.…”
mentioning
confidence: 99%